Signing of Grant Agreement with Mozambique: Contributing to the improvement of people’s living environment in Niassa Province through the construction of a rural water supply facility - JICA (2021)
On February 26, 2021, the Japan International Cooperation Agency (JICA) signed a grant agreement with the Government of the Republic of Mozambique in Maputo, to provide grant aid of up to 2.076billion yen for the Project for the Construction of a Rural Water Supply Facility in Niassa Province. Under this project, people’s living environment in Niassa Province will improve through installing a rural water supply facility, which will allow access to safe and clean water. It is expected that this project will lead to reduction of waterborne diseases and nutritional improvement. Measures to combat climate change will also be conducted, and this project will contribute to the achievement of SDGs Goals 3, 6, and 13.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; access to services / acesso a serviços; climate change / mudanças climáticas; infrastructure / infrastrutura

Food security and livelihoods under a changing climate in Mozambique: preparing for the future - World Food Programme (World Food Programme, 2021)
Mozambique’s climate is characterized by relatively uniform temperatures across the country and a north-south rainfall gradient which results in higher more reliable rainfall amounts in the North, and lower more variable rainfall amounts in the South Historical climate analysis for the country shows that temperatures are already increasing and rainfall trends are dominated by year-to-year variability. Livelihoods and agricultural production systems are already being affected by the changing and more variable climate. Climate projections for the 2050s show strong agreement for an increase in temperature, but no strong trend for changes in rainfall. All scenarios of projected climate change will result in increased heat stress, reductions in water availability, and more frequent and intense extreme weather events, which could exacerbate food insecurity in the absence of adaptation.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; climate change / mudanças climáticas; security / segurança